2009
DOI: 10.1210/jc.2008-1455
|View full text |Cite
|
Sign up to set email alerts
|

Serum Osteocalcin Level Is Associated with Glucose Metabolism and Atherosclerosis Parameters in Type 2 Diabetes Mellitus

Abstract: Serum osteocalcin is associated with glucose and total adiponectin levels, fat mass, and atherosclerosis parameters in patients with type 2 diabetes, suggesting that osteocalcin is important for not only bone metabolism but also glucose and fat metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
259
4
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(309 citation statements)
references
References 27 publications
40
259
4
6
Order By: Relevance
“…demonstrated an inverse correlation between higher levels of osteocalcin and mar kers of atherosclerosis (lower ankle-brachial in- dex and increased intima-media thickness), suggesting that osteocalcin might be implicated in the atherosclerotic disease (28). Other observational study in 102 patients younger than 40 years old identified a negative association between osteocalcin levels and acute myocardial infarction (29).…”
Section: Osteocalcin Levels and Metabolic Parameters In Humansmentioning
confidence: 96%
“…demonstrated an inverse correlation between higher levels of osteocalcin and mar kers of atherosclerosis (lower ankle-brachial in- dex and increased intima-media thickness), suggesting that osteocalcin might be implicated in the atherosclerotic disease (28). Other observational study in 102 patients younger than 40 years old identified a negative association between osteocalcin levels and acute myocardial infarction (29).…”
Section: Osteocalcin Levels and Metabolic Parameters In Humansmentioning
confidence: 96%
“…Indeed, levels of circulating osteocalcin have been inversely correlated with BMI, fat mass and plasma glucose levels in adult or elderly men and women of diverse ethnicities [26][27][28][29]. Additional studies have linked low osteocalcin to impaired levels of HbA 1c , fasting insulin and insulin resistance (estimated by the HOMA of insulin resistance HOMA-IR) in adult men and women, irrespective of whether they have diabetes [28,[30][31][32][33]. In contrast, serum osteocalcin has been positively correlated with the HOMA of beta cell function (HOMA-%B) in diabetic patients, before and after glycaemic control [33,34].…”
Section: Clinical Relevance Of the Osteocalcin-mediated Regulation Ofmentioning
confidence: 99%
“…Levels of circulating osteocalcin have also been associated with a number of lipid abnormalities. For instance, serum osteocalcin levels are inversely correlated with levels of adipocyte-specific fatty acid-binding protein (A-FABP) in a mixed population, and with levels of HDL-cholesterol in men, and are positively correlated with total adiponectin levels in post-menopausal women [27,31,34]. In addition, an association of decreased levels of osteocalcin with premature myocardial infarction in young patients or with coronary heart disease in older individuals have been reported [34,36].…”
Section: Clinical Relevance Of the Osteocalcin-mediated Regulation Ofmentioning
confidence: 99%
“…There is accumulating evidence that OC is also involved in glucose metabolism and insulin secretion (Oz et al 2006;Pedrazzoni et al 1989). Serum OC has been shown to be negatively correlated with (a) the degree of glucose intolerance (Bouillon et al 1995), (b) with fasting glucose in patients with diabetes and with homeostasis model assessment of insulin resistance (HOMA-IR; Kanazawa et al 2009), and (c) with systolic blood pressure in hypertensive postmenopausal women. Since there is sufficient evidence for a link between serum OC levels with metabolic syndrome and cardiovascular risk factors, OC should be considered not only a bone turnover marker but also an index of general health.…”
Section: Biochemical and Endocrine Serum Markersmentioning
confidence: 99%